2001
DOI: 10.1111/j.1744-7348.2001.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pericarp alpha‐amylase activity on wheat (Triticum aestivum) Hagberg falling number

Abstract: Pericarp alpha-amylase activity in wheat has largely been ignored as a potential cause of low Hagberg falling number (HFN) in the UK, because pericarp alpha-amylase enzymes have been thought too temperature-sensitive to affect HFN and are usually degraded by harvest. Nevertheless, there are several circumstances where immature grains may be present in harvested grain. Therefore, we tested the hypotheses that pericarp alpha-amylase enzymes in immature grains could lower HFN, but also that inactivation of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…(Olered & Jönsson, 1970). Lunn et al (2001) confirmed that the presence of pericarp isozymes has an effect on the HFN of wheat but more alpha-AMY-2 activity is required to reduce HFN compared with the alpha-AMY-1 activity due to the different adsorbent properties of alpha-AMY-1 and alpha-AMY-2.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…(Olered & Jönsson, 1970). Lunn et al (2001) confirmed that the presence of pericarp isozymes has an effect on the HFN of wheat but more alpha-AMY-2 activity is required to reduce HFN compared with the alpha-AMY-1 activity due to the different adsorbent properties of alpha-AMY-1 and alpha-AMY-2.…”
Section: Introductionsupporting
confidence: 52%
“…During germination or sprouting alpha-AMY-1 isozyme [also referred to as 'malt', high pI, Group 1 and GIII (Marchylo et al, 1980)] and alpha-AMY-2 to a lesser extent, are produced (Sargeant, 1980;Mrva & Mares, 2001b). The alpha-AMY-2 isozyme [also referred to as 'green', low pI, Group 2, GI and GII (Marchylo et al, 1980;Lunn et al, 2001)] is expressed in high concentrations in the pericarp of immature, green grains (Gale, 1989). The alpha-AMY-3 isozyme is also transiently expressed (Daussant & Renard, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations